Metabolic Profile and Hepatoprotective Efficacy of Carica Papaya Leaves in CCl4 Induced Oxidative Stress Albino Mice - Maryam Abdulkadir Usman; Hamza Ahmed Pantami; Muhammad Bappah Sani; Aliyu Ibrahim Lawan; Hajjagana Hamza (Indonesian Journal of Health Research and Development, 2025)
Background: Hepatic disorder is fatal and require vital medication, orthodox cure is deleterious, so there is need for natural curative agents.Aims: Bioactive phytochemical analysis and   efficacy of Carica papaya leaves extracts versus CCL4 induced oxidative stress in mice.Methods: The metabolite profile of Carica papaya leaves extract was analysed by LC-MS/MS analysis via GNPS. Liver aminotransferases were assessed, liver tissues and homogenates were assessed for histopathology and MDA, catalase, superoxide dismutase, and Glutathione S-Transferase activities, qRTPCR mRNA expression of hepatic tissue Glutathione S- Transferase was performed. Free radical scavenging activity of the extract were evaluated using invitro prototypes.Results: Numerous metabolites were identified from crude extract. Observed weight loss in rats, liver damage through elevating serum variables (marker enzymes and bilirubin), decrease in total protein and albumin. A significant decrease in tissue catalase, GST, and superoxide dismutase activities and marked increase in MDA level (p<0.05) were also observed. The extract effectively ameliorated CCl4 effects with marked decrease in serum variables. GST mRNA expression of hepatic tissue and histopathological results also supported the biochemical findings. Extract exhibited radical scavenging activity with DPPH IC50 of 0.56mg/ml, FRAP IC50 of 0.52mg/ml, H2O2 IC50 of 0.58mg/ml and Phosphomolybdenum IC50 of 0.62.Conclusion: Carica papaya leaves was beneficial in modulating the alterations induced in liver and serum variables of mice in CCL4 induced oxidative stress.